PENARI WANITA PADA TARI GAGAH JEMPARINGAN: SEBUAH TINJAUAN ESTETIKA - Alfi Mazidah Khafidz; RM Pramutomo; Maharani Lutvinda Dewi (TAMUMATRA, 2025)
Jemparingan dance is a dance that emphasizes the strength and agility of a soldier, jemparigan dance depicts two soldiers who are practicing using properties or weapons in the form of Gendhewa (bow) and keris, created in 1979 by Sunarno Purwolelono and the dance music was created by Blacius Subono. The purpose of this research is to find out (1) how the form of Jemparingan Dance danced by women, and (2) how the aesthetics of Jemparingan Dance danced by women, with the method of participatory observation, and interviews. This research explains the calm form and aesthetics contained in Jemparingan Dance danced by women.